ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESULITAN BELAJAR SISWA MATERI NILAI-NILAI PANCASILA MATA PELAJARAN PPKn SMAN 7 PONTIANAK - Gita Oktavianti; Bambang Budi Utomo; Thomy Sastra Atmaja (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed at determining the factors that affect students’ learning difficulties in understanding the learning material about the values of Pancasila in the administration of government, the PPKn subject in 10 th -grade of Mathematics and Natural Sciences in SMAN 7 Pontianak. The method used in this study is descriptive with qualitative form. The data were collected using direct observation technique, interview, and documenter study technique. The subjects in this study were the teacher of the PPKn subject and the 10 th -grade students Mathematics and Natural Science 4, resulted in the data obtained in  the form of the interview result. The findings indicated that there were external and internal factors affecting students’ learning difficulties in understanding the material. Internal factors included intelligence and learning success, learning attitudes, motivation, concentration, habits, and physical health, as well as external factors, consist of the teaching methods, school discipline, and social environment such as peers.Keywords: Factors in Learning Difficulties, PPKn, Values of Pancasila